Pengaruh Variasi Sudut Mata Pisau Mesin Pengupas Kelapa MudaTerhadap Kapasitas Produksi Berdasarkan Tingkat Daya Listrik Motor Penggerak - Toni Haikal Saputra; Ikhwanul Qiram; Gatut Rubiono (Virtual of Mechanical Engineering Article, 2022)
Abstract The characteristics of young coconut skin, which has high fiber content, are often an obstacle factor in the peeling process. Setting the rotation speed and angle of the slicing knife are important parameters that affect the cutting style of the coconut peeler knife. This study aims to determine the production capacity, electrical power requirements, and physical quality of the peeling results on the young coconut peeler machine. The experiment was carried out using variations in the sharpness of the blade angle, namely 10o, 15 o, and 25 o. Young coconut material is selected with relatively the same diameter and weight. The results showed that the knife angle variation of 15o had the highest production capacity of 499 pieces/hour. Research on economic analysis generates Rp. 1.093/hour while for electric power or the cost of electricity required per unit is Rp. 19/piece. This research can be concluded that the variation of the angle of the blade that has optimum performance is shown in the variation of the angle of 15 o. Keywords: Machine, Young Coconut, Angle Variation, Production Capacity.